Alternative splicing and genomic structure of the Wilms tumor gene WT1. - Haber, D A (1991)
The chromosome 11p13 Wilms tumor susceptibility gene WT1 appears to play a crucial role in regulating the proliferation and differentiation of nephroblasts and gonadal tissue. The WT1 gene consists of 10 exons, encoding a complex pattern of mRNA species: four distinct transcripts are expressed, reflecting the presence or absence of two alternative splices. Splice I consists of a separate exon, encoding 17 amino acids, which is inserted between the proline-rich amino terminus and the zinc finger domains. Splice II arises from the use of an alternative 5' splice junction and results in the insertion of 3 amino acids between zinc fingers 3 and 4. RNase protection analysis demonstrates that the most prevalent splice variant in both human and mouse is that which contains both alternative splices, whereas the least common is the transcript missing both splices. The relative distribution of splice variants is highly conserved between normal fetal kidney tissue and Wilms tumors that have intact WT1 transcripts. The ratio of these different WT1 mRNA species is also maintained as a function of development in the mouse kidney and in various mouse tissues expressing WT1. The conservation in structure and relative levels of each of the four WT1 mRNA species suggests that each encoded polypeptide makes a significant contribution to normal gene function. The control of cellular proliferation and differentiation exerted by the WT1 gene products may involve interactions between four polypeptides with distinct targets and functions.